KONTRIBUSI SISTEM IT SUPPORTING DAN PENGUATAN KUALITAS PEMBELAJARAN TERHADAP MUTU SEKOLAH DASAR - Saribulan (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2024)
This study aims to examine the influence of IT supporting and learning quality on the quality of Elementary Schools in Biringkanaya District, Rapocini District and Tamalate District in Makassar City with a sample of 244 teachers and educators. This study consists of three variables, namely IT supporting, learning quality and elementary school quality. The analysis method used in this study is correlation analysis and t-test. This study found that there is a strong and significant IT supporting and learning quality on elementary school quality. The largest correlation occurs between the quality of learning and the quality of schools at 0.798, IT supporting with a correlation value of 0.659. IT supporting and the quality of learning are two main pillars in improving the quality of schools. IT supports efficiency and accessibility, while quality learning ensures meaningful and relevant educational outcomes.